2019
DOI: 10.1016/j.heliyon.2019.e02533
|View full text |Cite
|
Sign up to set email alerts
|

Association of the retrospective self-report ratings with the dynamics of EEG

Abstract: The neural underpinnings of subjective experience during resting state remain elusive. Dynamic features of EEG oscillations may provide more understanding of the relationship between the content of inner conscious experience and electrical brain activity. We tested a correlation of rating on the Amsterdam Resting-State Questionnaire (ARSQ) with dynamic parameters of EEG recorded in 49 healthy volunteers during the 10-min resting session. The participants filled ARSQ immediately after the rest. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Similarly, based on the initial observation by Diaz et al [ 16 ], it is expected that at least one f-PC in the theta frequency range (4–7.5 Hz) is positively correlated with the ARSQ domain of Sleepiness. Finally, in line with the report by Portnova et al [ 22 ], we anticipate that at least one of the alpha f-PCs is positively associated with the ARSQ domain of Planning. We also evaluate other possible associations between distinct f-PCs and the domains of the ARSQ.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similarly, based on the initial observation by Diaz et al [ 16 ], it is expected that at least one f-PC in the theta frequency range (4–7.5 Hz) is positively correlated with the ARSQ domain of Sleepiness. Finally, in line with the report by Portnova et al [ 22 ], we anticipate that at least one of the alpha f-PCs is positively associated with the ARSQ domain of Planning. We also evaluate other possible associations between distinct f-PCs and the domains of the ARSQ.…”
Section: Introductionsupporting
confidence: 92%
“…No associations were observed with components in the delta and beta frequency ranges, although Portnova et al [ 22 ] previously reported a negative correlation between the power spectrum density from 2–3 Hz and Planning. However, it should be noted that both the extracted D1 (peaking at 0.5 Hz) and B1 (peaking at 17 Hz) components were somewhat different from those reported previously: D1 resembled activity over the left frontal area, peaking at the FP1, AF7, and F7 electrodes, while reports in the literature have observed maximum activities in the central, fronto-central, and right frontal areas [ 40 , 41 , 67 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The ARSQ covers ten resting-state cognition domains: Discontinuity of Mind (DoM), Theory of Mind (ToM), Self, Planning, Sleepiness, Comfort, Somatic Awareness (SA), Health Concerns (HC), Visual Thought (Vis) and Verbal Thought (VT) [12,13]. This tool has been successfully applied in neuroimaging studies, including those using EEG [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%